2017
DOI: 10.1186/s12870-017-1090-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a major QTL for salt tolerance of mature field-grown maize plants based on SNP markers

Abstract: BackgroundSalt stress significantly restricts plant growth and production. Maize is an important food and economic crop but is also a salt sensitive crop. Identification of the genetic architecture controlling salt tolerance facilitates breeders to select salt tolerant lines. However, the critical quantitative trait loci (QTLs) responsible for the salt tolerance of field-grown maize plants are still unknown.ResultsTo map the main genetic factors contributing to salt tolerance in mature maize, a double haploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…A QTL analysis of agronomic traits over the whole‐growth duration under salt stress has not been reported in sorghum. Fortunately, some research on QTLs related to salt tolerance in the whole growth stages has been conducted in barley, rice and maize (Chai et al, ; Eleuch et al, ; Luo et al, ; Rao, John, & Kumar, ; Sbei et al, ; Xue et al, ), and these studies provide methods for evaluating salt tolerance in the mature stage. In the evaluation of salt tolerance in the late growth stage, many parameters including agronomic and physiological traits have been used as indicators of the effect of salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…A QTL analysis of agronomic traits over the whole‐growth duration under salt stress has not been reported in sorghum. Fortunately, some research on QTLs related to salt tolerance in the whole growth stages has been conducted in barley, rice and maize (Chai et al, ; Eleuch et al, ; Luo et al, ; Rao, John, & Kumar, ; Sbei et al, ; Xue et al, ), and these studies provide methods for evaluating salt tolerance in the mature stage. In the evaluation of salt tolerance in the late growth stage, many parameters including agronomic and physiological traits have been used as indicators of the effect of salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…SSR markers have been used to scan crop genomes to identify markers associated with salt tolerance in cotton (Zhao et al 2016) and cucumber (Kere et al 2017). In maize, Luo et al (2017) mapped the QTLs for salt tolerance using a doubled haploid population and high-density SNP markers. The authors isolated major QTLs for salt tolerance and identified two candidate genes involved in ion homeostasis.…”
Section: Qtlomics Of Salt Tolerancementioning
confidence: 99%
“…ZmNHX8 was upregulated in NaCl treatment, but ZmNHX4 , - 5 , and -11 were downregulated in root. NHX7/SOS1 is critical for excluding Na + from plant roots [51] and ZmNHX2 is associated with a major quantitative trait locus (QTL), qST1 , which confers salt tolerance on maize plants [52, 53]. Upregulated expressions of ZmNHX8 in our salinity treatment support the idea that their roles in response to salt stress may be conserved in maize.…”
Section: Discussionmentioning
confidence: 66%